Blood lactate concentration following maximum exercise in trained subjects. Issue 3 (September 1981) - Gass, G. C.; Rogers, S.; Mitchell, R.
Abstract : The time when blood lactate reaches peak concentration following maximum exercise is unclear. The post exercise venous blood lactate concentration was determined serially for 30 minutes in 13 trained men following maximum exercise on a motor driven treadmill. Lactates were determined enzymatically in duplicate. The VO2 max and percent body fat was 65.1 +/- 4.8 ml.kg-1.min-1 and 11.4 +/- 1.4, respectively. The venous lactate reached a peak concentration at the 6th minute (14.2 mmol.L-1) of an inactive recovery, and declined linearly thereafter to reach a concentration of 7.43 +/- 0.60 mmol.L-1 at the 30th minute. The net rate of lactate removal was .30 mmol.L-1.min-1. Statistical analysis found no significant difference in lactate concentration during the 4th, 5th and 6th minute post exercise, indicating that these post exercise times may be appropriate to sample venous blood for peak lactate concentration.